(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
The aim of this study is to gain more knowledge about the materials and teaching strategies used by an English teacher in Uzbekistan to teach seventh-grade students speaking. It was conducted using a case study research design. The study’s instruments are the observation logs, interview questions, and documentation. Every step of the English teaching process for the seventh-grade class is observed by the researcher. The researcher also conducted interviews with five students and five teachers to get more data. The paperwork is used to verify the data from the observations. The study’s results show that English teachers use a range of teaching techniques, such as question-answer display, translation, drilling, and debate.